Perspective: Presuming Autistic Communication Competence and Reframing Facilitated Communication - Heyworth, Melanie; Chan, Timothy; Lawson, Wenn (Frontiers in Psychology, 2022)
Debate surrounding the validity of the method of supported typing known as facilitated communication (FC) has been continuous since its inception in the 1990s. Views are polarized on whether FC can be considered an authenticated method for use by people with complex communication needs (CCN) or significant challenges in speech, language and communication. This perspective article presents an analysis of the research arguing for – and against – the use of FC, combined with the lived experience knowledge of autistic adults who utilize FC, to rehabilitate its current standing as discredited and unevidenced. By considering extant qualitative and quantitative studies, as well as personal accounts of the use of this particular Augmentative and Alternative Communication (AAC) method, the authors argue that the current dismissal of FC is rooted in ableist and outdated approaches. FC research should be reconsidered and reconducted using current best practice autism research approaches, including coproduction and a presumption of autistic communication competence, to assess its validity as a potential AAC method for autistic individuals.